Notes on the earthworm species, Metaphire anomala (Michaelsen, 1907) (Clitellata, Megascolecidae) in Southern Vietnam, with descriptions of two new species - Nguyen, Tung T.; Lam, Dang H.; Nguyen, Anh D. (European Journal of Taxonomy, 2021)
Integrative taxonomy was employed to exploit the differences between the known Metaphire anomala (Michaelsen, 1907) and other specimens collected in Vietnam. The results brought to light two new species, namely Metaphire iranomala sp. nov. and Metaphire decemtheca sp. nov. The former is easily recognised by having male pores on xix and four pairs of spermathecal pores on 5/6/7/8/9 while the latter is distinguished by having five pairs of spermathecal pores on 4/5/6/7/8/9. The K2P distances of the fragment of the cytochrome c oxidase subunit I (COI) gene are 13.1% between M. iranomala sp. nov. and M. anomala (Michaelsen, 1907) and 18% between M. decemtheca sp. nov. and Metaphire grandiverticulata Nguyen & Lam, 2017. The intraspecific divergences are 1.5%–10.6% for M. iranomala sp. nov. and 2.1%–11.4% for M. decemtheca sp. nov.